Intergenerational mobility, human capital accumulation, and growth in India - Roy van der Weide; Melinda Vigh (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2018)
Productivity and socio-economic progress are inter-connected. Economic growth funds policies that promote socio-economic progress, while the latter serves as a growth engine. A society with high mobility is one where individual achievements are influenced less by the individual's parents and more by her potential. In an application to 54 state-regions in India (1983-2011), we identify the causal effect of intergenerational mobility on household expenditure's future growth. We find that intergenerational mobility has a positive effect on growth, particularly among the poor. Furthermore, mobility is found to be positive for human capital accumulation except for individuals with highly educated parents for whom it matters less whether the playing field is level or not.
Keywords: D31; D63; E24; O15; O40; 330; intergenerational mobility; inequality; growth; poor; India